Meningkatkan Kesadaran Pentingnya Tanda Daftar Usaha bagi Pelaku Usaha Rumahan melalui Penyuluhan Door to Door di Wilayah Margaluyu - Noerma Kurnia Fajarwati; Kurnia Dwi Sari Utami; Akbar Marzuqi; Aldi Prayuga; Meita Rahayu; Mirna Sumyati; Siti Nurhamilah; Imelia Putri (Fakultas Teknik Universitas Cenderawasih, 2024)
Business Registration Certificate (TDU) is an essential element in strengthening the legality and sustainability of small businesses, particularly in providing legal protection as well as access to funding and training opportunities. Increasing awareness of the importance of TDU among home-based entrepreneurs is a crucial step in reinforcing the legality and sustainability of small enterprises, especially in the Margaluyu region. The primary focus of this activity is to enhance understanding of the benefits of TDU, including legal protection and access to various opportunities such as funding and training. Direct engagement with entrepreneurs allows for the identification of their specific needs and challenges. Through a door-to-door outreach approach, this program aims to provide a deep understanding of the benefits of TDU, ranging from legal protection aspects to access to funding and training opportunities. By involving entrepreneurs directly, this method effectively addresses the specific needs and challenges faced by home-based businesses in Margaluyu. The results of this outreach indicate an increase in understanding and participation among entrepreneurs in legally registering their businesses, which is expected to promote more sustainable local economic growth.